JoJo's bizarre adventure. Part 6, Stone ocean. Volume 8 - Araki, Hirohiko, 1960- (Shonen Jump manga., 2025)
Weather Forecast's memories have been restored, and he is not happy. He unleashes his full power against Pucchi and Pale Snake, but others are caught in the crossfire of his attack. Can Jolyne and the rest of her friends reach the two men unscathed? Weather Forecast seems to have Pucchi on the ropes though, and it finally looks like his good fortune has run out, but the bad priest won t go down easily not when he is so close to reaching Heaven.